The application of Kahoot as an online assessment tool to foster student’s engagement: Student’s experiences and voices - Wahyuni, Sri; Etfita, Fauzul (Register Journal, 2023)
The advancement of technology has an impact on numerous aspects, including assessment. Students tend to feel bored, nervous, and anxious while doing the test. Consequently, the educators are required to create a meaningful atmosphere in the classroom. Kahoot can be used as an alternative assessment tool. The purpose of this study was to gain knowledge about the students’ voices and experiences with the use of Kahoot as an assessment tool in their English grammar class at the end of each of the fourteen meetings. This research was conducted at a private university in Riau with seventy-five participants in the English language education study program. This research was descriptive-qualitative by applying a questionnaire and interview. The findings show that most of the respondents are giving positive responses to using Kahoot as an assessment tool. The result of the research revealed that Kahoot is more preferred by the students than a paper-based test, which offers challenges, an interactive interface, sound, and music, helps students focus on the subject, and increases their interest and motivation. Meanwhile, the researcher found that the weaknesses of Kahoot are the time limit given and the unstable internet connection. Overall, the researcher suggests employing Kahoot as an assessment tool to boost students’ engagement.